UNSUPERVISED MACHINE LEARNING FOR SEISMIC ANOMALY DETECTION: ISOLATION FOREST ALGORITHM APPLICATION TO INDONESIAN EARTHQUAKE DATA - Gregorius Airlangga (LPPM Universitas Bina Bangsa, 2023)
Indonesia's position on the seismically active Pacific